Effects and implications of the COVID-19 pandemic on medicine use by employees of a Brazilian public university: a cross-sectional study - Paula, Waléria de; Oliveira, Wanessa Cecília de; Meireles, Adriana Lúcia; Nascimento, Renata Cristina Rezende Macedo do; Silva, Glenda Nicioli da (São Paulo Medical Journal, 2022)
BACKGROUND: During the COVID-19 pandemic, universities have had to adopt remote education, a strategy that caused sudden changes of routine for everyone involved in academia. OBJECTIVE: To assess the profile of medicine use by the employees of a Brazilian public university during the COVID-19 pandemic. DESIGN AND SETTING: Cross-sectional study at a Brazilian public university. METHODS: Employees were invited to answer an online self-administered questionnaire, containing questions on sociodemographic features, medicine use, mental health and lifestyle habits during the COVID-19 pandemic. The outcome variable was the use of medicines stratified according to occupation. Descriptive, bivariate and multivariate (Poisson regression) statistical analyses were performed. RESULTS: A total of 372 employees participated in the study and use of medicine was reported by 53.2%. Among professors, suicide attempts (prevalence ratio [PR], 1.81; 95% confidence interval [CI], 1.20-2.74), physical activity (PR, 1.53; 95% CI, 1.11-2.11) and poor self-rated health (PR, 1.29; 95% CI, 1.01-1.66); and among technicians, decreased workload during the COVID-19 pandemic (PR, 1.41; 95% CI, 1.00-1.99), excess body weight (PR, 1.39; 95% CI, 1.02-1.88) and poor self-rated health (PR, 1.48; 95% CI, 1.14-1.92) werepositively associated with use of medicines. In addition, among technicians, engaging in physical activity (PR, 0.60; 95% CI, 0.46-0.78) was a protective factor against medicine use. CONCLUSION: The profile of medicine use among these employees was similar to that of the Brazilian population. However, some associated factors may have been influenced by the COVID-19 pandemic, thus highlighting the need to examine this topic in a longitudinal study.